Espaços de transição: entre a arquitetura e a cidade - Balsini, Andre Reis (2014)
Our object of study will be the intermediate space between architecture and the city, the transitional space between inside and outside, private and public. Environments that combine characteristics of opposites means; potentially allowing an interpenetration between architecture and urban space. In our research, we should address of the possibilities and implications in the architecture design, thereof touches to their transitional elements. The study seeks to expand a conceptual field and proposes an interlocution with a series of authors which have looked into the thematic of transitional space and (or) near concepts, complementary, from which we intend to situate ourselves with the discussion concerning of binomials architecture-city, individual-collective, singular-plural, among others. To counteract the concepts investigated a reading of concrete architectural objects, we selected five referential buildings - of public character - in the cities of São Paulo and Rio de Janeiro, and analyze how the interventions made from the architectural object could result in environments of assemblage, which to have integrated into the urban tissue, and have amplified the possibilities of public space for collective use. Thus, we presented in dissertation, initially, a diversity of approaches to the research object, in order to establish some fundamental considerations for the architecture design of the space of transition. Following, we discuss briefly the question of the project, from the perspective of his own ambivalence of propositive instrument. Completing the study, we explore the unfoldings of the thematic from object, listing five qualitative themes through which we oriented the discussions, in which projective and theoretical referentials were inserted.